Pelatihan Dalam Meningkatkan Keterampilan Dasar Mengajar Guru di Rumah Belajar PATMOS - Janwar Tambunan; Lois Oinike Tambunan (Departement of Mathematics Education, 2024)
The aim of implementing teaching and learning is to achieve learning achievement, both in terms of process and in achieving results which are always influenced by various factors. In teaching students, teachers have the ability to organize and handle students in learning, so that when studying students can follow the lesson well. In this case, teachers really need basic teaching skills. The aim of this community service is to find out about the essence of basic teaching skills. Basic teaching skills have several aspects of skills including: 1) skills to open and close lessons, 2) skills to explain, 3) skills to ask questions, 4) skills to guide small group discussions, 5) skills to manage the class, 6) skills to provide reinforcement, 7) skills holding variations, 8) small group and individual teaching skills.